Personality psychopathology differentiates risky behaviors among women with bulimia nervosa. Issue 7 (15th June 2016) - Pearson, Carolyn M.; Pisetsky, Emily M.; Goldschmidt, Andrea B.; Lavender, Jason M.; Wonderlich, Stephen A.; Crosby, Ross D.; Engel, Scott G.; Mitchell, James E.; Crow, Scott J.; Peterson, Carol B.
ABSTRACT: Objective: Individuals with bulimia nervosa (BN) frequently endorse risky behaviors such as self‐harm and substance use. However, no studies of BN to date have examined factors associated with engaging in individual or co‐occurring risky behaviors. Given that individuals with BN often have personality psychopathology, which has been linked to symptoms and course of illness, this study sought to examine how personality may differentiate engagement in risky behaviors among BN individuals. Method: A sample of 133 women with BN completed self‐report measures of personality psychopathology at baseline, and then reported on bulimic and risky behaviors (e.g., substance misuse, self‐harm) over 2 weeks using ecological momentary assessment. A series of hierarchical multiple regression analyses were conducted to examine the unique associations between state‐level predictor variables (each risky behavior, e.g., substance misuse, and combination of risky behaviors, e.g., substance misuse plus self‐harm) and trait‐level personality constructs. Results: Substance misuse behavior, above and beyond all other risky behaviors, was significantly associated with higher scores on trait dissocial behavior ( P  = 0.004). Discussion: Substance misuse in BN has a unique association with dissocial behavior, a personality trait characterized by hostility, impulsivity, and entitlement. These results suggest that targeting personality variables may help facilitate more effective treatment of risky behaviors, including substance use in BN. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:681–688)